Specific characteristics of sponsorship contract - Tone Jagodic; Zlatko Mateša (Zbornik Radova Pravnog Fakulteta u Splitu, 2022)
Sponsorship contract represents one of the legal backgrounds which is commonly used in modern sport. As a relatively “young” and quite specific contract it has not been codificated yet. The causa of a sponsorship contract is linked to the expectations of both parties of the contract at the time of the conclusion of the contract. As a bilateral contract of obligation, sponsorship has a strong economic background which is the leverage for the conclusion of the contract. A definition that highlights the characteristics of sponsorship contains the International Chamber of Commerce Advertising and marketing communication Code. There are several different elements of the definition which characteristically represent the essence of the sponsorship relationship. Among them are the mutual benefit of the sponsor and sponsored entity, providing of finance or other support, ambition to establish an association between the sponsor’s image, brands or products and a sponsorship property, return for rights, promotion of the association between parties, grant of certain agreed direct or indirect benefits, and some others. In the article there are explanations of different above elements. It seems that the above parameters are the essence of the sponsorship agreement which also reflects the basic elements of the definition of the ICC sponsorship agreement. The ICC definition provides a basis that fully captures the typical elements of a sponsorship contract and which could lead to future efforts in terms of finding the right definition for a possible legal codification of the sponsorship contract. From the sponsor’s point of view, sponsorship represents an attempt to identify with the value of the sponsored entity, the purpose of which is further manifested by the promotion of this link, both leading to the sponsor’s objective of raising or improving its image in the public or in society. The key here is the ability of the sponsor to turn a challenge into an opportunity, which is then exploited. The opportunities must outweigh the challenges, which is the original motive of the sponsor in the sponsorship contract.